2014
DOI: 10.4049/jimmunol.1303213
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Pathway Activates Robust Autophagy-Dependent Unconventional Protein Secretion in Human Macrophages

Abstract: Dectin-1 is a membrane-bound pattern recognition receptor for β-glucans, which are the main constituents of fungal cell walls. Detection of β-glucans by dectin-1 triggers an effective innate immune response. In this study, we have used a systems biology approach to provide the first comprehensive characterization of the secretome and associated intracellular signaling pathways involved in activation of dectin-1/Syk in human macrophages. Transcriptome and secretome analysis revealed that the dectin-1 pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 51 publications
2
69
1
Order By: Relevance
“…1C). We have previously shown that TLR4 activation by extracellular LPS does not induce EV-mediated protein secretion in human macrophages (16). In contrast to this, the current results strongly suggest that intracellular LPS is a potent activator of EV-mediated protein secretion.…”
Section: Fig 1 Intracellular Lps Recognition Pathway Activates Robucontrasting
confidence: 56%
See 2 more Smart Citations
“…1C). We have previously shown that TLR4 activation by extracellular LPS does not induce EV-mediated protein secretion in human macrophages (16). In contrast to this, the current results strongly suggest that intracellular LPS is a potent activator of EV-mediated protein secretion.…”
Section: Fig 1 Intracellular Lps Recognition Pathway Activates Robucontrasting
confidence: 56%
“…For this, macrophages were mock-transfected or transfected with LPS for different time periods, and the cell culture supernatants were collected and concentrated. The total secretome was separated into two fractions as follows: enriched extracellular vesicle (EV) fraction and rest-secretome (RS) fraction using sizeexclusion centrifugation as described previously (16). After this, the proteins in EV and RS fractions were separated by SDS-PAGE and visualized with silver staining.…”
Section: Fig 1 Intracellular Lps Recognition Pathway Activates Robumentioning
confidence: 99%
See 1 more Smart Citation
“…A major issue with this model is that the authors were unable to localise IL-1b to multivesicular bodies or exosomes, either before or after release. Another study was similarly unable to detect mature IL-1b/18 in exosomes purified from stimulated human macrophages [20]. Further, a later study by the Dubyak group showed that ATP-dependent secretion of MHC-IIcontaining exosomes does not require caspase-1 [21], but numerous reports have documented the requirement for caspase-1 for IL-1b secretion [7,15,22].…”
Section: Secretory Lysosomes Microvesicles and Exosomesmentioning
confidence: 98%
“…Processed caspase-1 (p20) is reduced in cell extracts upon stimulation of autophagy (27). As described above, once the inflammasome is activated, autophagy contributes to the unconventional secretion of IL-1β as well as IL-18 and HMGB1 (17,18). An alternative can come directly from intracellular bacteria (38,39).…”
Section: Autophagy Regulates Inflammationmentioning
confidence: 99%